Tugas dan Tanggungjawab Istri Seorang Gembala yang Ditinggal Mati Suami terhadap Efektivitas Pelayanan di Gereja Penyebabaran Injil Muliorejo - Christina Sianturi; Junjungan Simorangkir; Iwan Setiawan Tarigan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is motivated by the leadership of the wife of a pastor whose husband died in continuing the transition of service as pastor of the congregation. After the death of the husband who was the church pastor, the duties and responsibilities of church ministry were automatically assigned to the wife as the continuing pastor. After being approved as continuing pastor, the wife will play a very important role, her role will be the same as the previous pastor, carrying out congregational pastoral services such as pulpit service, embracing, guiding, nurturing, serving and leading as well as building relationships with congregation members and servants. The differences in leadership of wives whose husbands die will be directly visible when carrying out their duties and responsibilities as pastors of the congregation which will have an impact on the effectiveness of the ministry. Therefore this research takes the topic “duties and responsibilitities of a pastor’s wife whose husband dies on the effectiveness of services at the muliorejo gospel spreading church”. With the aim of the research to determine and analyze the transition of duties of a pastor's wife whose husband died on the effectiveness of service at the muliorejo gospel spreading church and to find out and analyze the responsibilities of a pastor's wife whose husband has died regarding the effectiveness of the ministry at the muliorejo gospel spreading church. This research was conducted using descriptive qualitative methods, the data obtained in this research used an interview approach and recorded conversations via cellphone recordings with 12 informants. The conclusion obtained from this research is that there was a change in duties experienced by the wife of a shepherd whose husband died, this change was due to a change in duties with a different position status. From previously only being a companion to her husband who was the pastor of the congregation, she has now become a continuing pastor because of her husband's death. With the task that the mother shepherd received as continuing shepherd at the muliorejo gospel spreading church making him a person who is full of love, has a high caring nature, is firm in leading and practicing a holy life so as to support the effectiveness of ministry in the church. The leadership responsibility of a pastor's wife whose husband has died directly contributes to the effectiveness of the ministry at the muliorejo gospel spreading church. The effectiveness of the service that occurs at the muliorejo gospel spreading church is carrying out physical construction of the church, experiencing an increase in the number of souls, increasing church activity programs and opening a new church branch which will be ratified on May 5, 2024.